Outdoor Education A Pathway to Experiential, Environmental, and Sustainable Learning - Schroth, Stephen T. (Cham : Springer International Publishing : Imprint: Palgrave Macmillan, 2023)
"This is a superb book, and does a wonderful job of relating the current state of research related to outdoor, environmental, and place-based education. The book provides a roadmap showing others to identify problems, develop research questions, put together data, and disseminate information to third parties." -Joan Franklin Smutny, Founding Director of the Center for Gifted, a Northern Illinois University Partner, and Director of the Midwest Torrance Center for Creativity This book explores the phenomenon of outdoor education, an approach that permits children from all backgrounds to explore environmental, sustainability, and other issues facing them and their communities. Organized around both the conceptual and the practical issues facing school leaders interested in outdoor education, the book provides a wealth of resources for those interested in implementing outdoor education in their schools or classrooms. Infinitely flexible, outdoor education provides a lens through which teachers may explore any content area with any age group of children. Providing readers with both the theoretical underpinnings that support place-based curriculum as well as practical ways to implement an outdoor education program, the book also provides seven case studies that examine the issues facing school leaders desiring to make such a change. It guides those interested in exploring outdoor education through the curricular, instructional, and policy considerations needed to accomplish this goal. Stephen T. Schroth is Professor of Early Childhood Education/Gifted & Creative Education at Towson University, USA. He is the author of eight monographs, multiple book chapters, and numerous articles, and has taught pre-service teachers and graduate students for over twenty five years.
Chapter 1. Continual School Reform -- Chapter 2. Curriculum Development -- Chapter 3. Children and the Outdoors: The Theoretical Underpinnings -- Chapter 4. Outdoor Education & Its Benefits for Diverse Learners -- Chapter 5. Outdoor Endeavors and Group Dynamics -- Chapter 6. Creativity & Outdoor Education -- Chapter 7. Fostering Positive Change -- Chapter 8. Resistance to Change -- Chapter 9. Conclusion.
Keywords: Outdoor education; Alternative Education; Holistic education; Outdoor Education; Alternative Education; Experiential Education; Holistic Education